Intorno a “Lingua e potere nel diritto dell’amministrazione pubblica” di Luigi Benvenuti: un punto di vista filosoficogiuridico - Puppo, Federico (Teoria e Critica della Regolazione Sociale / Theory and Criticism of Social Regulation, 2020)
By reviewing a book by Luigi Benvenuti (entitled Lingua e potere nel diritto dell’amministrazione pubblica), the author develops three main, although brief, considerations: at first, on the notion of complexity and legal order in connection with legal method; then, on rationality, in connection with the analysis of the Aristotelian principle of non contradiction and its ontological value; finally, on language and thought, in connection with a certain unexpected newness of the Aristotelian concept of man as “political animal”. The aim is to argue in favor of, so to say, a metaphysical account of truth and law. Keywords: order, method, Aristotle, logic, language.